Field-oriented control of ASM – comparison between simulated and measured performance - Blomqwist , Jonathan; Björfelt, Albin (My University, 2024)
Abstract The goal of this degree project was to control an induction machine in real-time with dSPACE and to compare the performance difference between the real machine and a simulated test. The work was conducted within a larger cooperation project with Volvo Cars. The aim was to improve simulation accuracy of induction machines. The controls and the simulations for this project were created in Simulink. The performance test was carried out in a laboratory environment using dSPACE to control the machine in real time. Important findings for the control were that anti-windup was needed for the PI-regulators and that the flux strongly influenced the performance. For the performance test it was found that the reactive input power for the real machine was twice as high at no-load as for the same test in the simulation. Under load, active input power was two times greater for the simulated test compared to the measurements on the real induction machine. Torque ripple was large for the real machine but it was stable in the simulations. The reasons for the differences between the real machine and the simulations were not investigated further.
Keywords: Keywords: Induction machine, Field-oriented control, V/Hz, Simulation, dSPACE, Simulink, Performance test, Real-time control